Hubungan Kebiasaan Makan terhadap Kejadian Anemia pada Remaja Putri di SMA Negeri 2 Demak - Anisa Nurhidayah; Tia Nurhanifah; Desi Soraya (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Iron deficiency anemia can be caused by several factors, namely from lack of consumption of food sources containing protein and iron, blood loss and unstable absorption, it can be said to be anemia if the hemoglobin level is <12 gr/dl. Was to find out the relationship between eating habits and the incidence of anemia in adolescent girls at SMA N 2 Demak. In this study uses a quantitative approach with a cross sectional approach with tools in the form of eating habits questionnaires. Population and Sample in this study were 65 adolescent female respondents who were anemic. The sampling technique in this study uses total sampling, which will be analyzed data with sperman rank correlation. Of this study were obtained from 65 respondents, 33 respondents (50.77%) had bad eating habits and moderate anemia 24 respondents (36.92%), from the analysis of bivariate significant values (p=0.000) < (0.05) then Ha was accepted and Ho was rejected, meaning that there was a relationship between eating habits and the incidence of anemia, The Rho (r) value obtained by -0.421 indicates that the direction of the relationship is negative or not unidirectional, which means that if the eating habits are bad, the incidence of anemia will be higher. Poor eating habits can affect the incidence of anemia in adolescent girls. Is expected to be a reference for schools to conduct routine Hb checks for counseling on the prevention of anemia in adolescent girls.